NewFlow's blog

By NewFlow, history, 4 months ago, In English,

$$$a_1 = 1$$$
$$$a_2 = 5$$$
$$$a_n = a_{n-1} + n^2(a_{n-2}+1)$$$

Prove $$$a_n=(n+1)!-1$$$
P.S. Original problem

 
 
 
 
  • Vote: I like it
  • 0
  • Vote: I do not like it

»
4 months ago, # |
  Vote: I like it 0 Vote: I do not like it

Auto comment: topic has been updated by NewFlow (previous revision, new revision, compare).

»
4 months ago, # |
  Vote: I like it +5 Vote: I do not like it

Putting $$$n = 1$$$ we get $$$a_1 = (1 + 1)! - 1 = 1$$$.

Putting $$$n = 2$$$ we get $$$a_2 = (2 + 1)! - 1 = 6 - 1 = 5$$$.

Now let the given statement is true for each $$$k < n$$$, let's prove this for $$$k = n$$$. $$$a_n = a_{n - 1} + n^2(a_{n - 2} + 1)$$$, then $$$a_n = n! - 1 + n^2((n - 1)! - 1 + 1) = n! - 1 + n^2 \cdot (n - 1)! = n! - 1 + n \cdot n! = n! \cdot (n + 1) - 1 = (n + 1)! - 1$$$. So, the statement is true for $$$k = n$$$.

By the principle of mathematical induction this is true for each $$$n > 1$$$.

»
4 months ago, # |
  Vote: I like it 0 Vote: I do not like it

Auto comment: topic has been updated by NewFlow (previous revision, new revision, compare).